Of PCOS Symptoms, Hirsutism Has the Most Significant Impact on the Quality of Life of Iranian Women - Khomami, Mahnaz Bahri; Tehrani, Fahimeh Ramezani; Hashemi, Somayeh; Farahmand, Maryam; Azizi, Fereidoun (PLOS ONE, 2015)
Introduction Polycystic ovary syndrome is a common endocrine disorder affecting women both physically and psychologically and can lead to a poor quality of life compared to their normal counterparts. The aim of the present study was to assess the impact of various clinical features of polycystic ovary syndrome on the health-related quality of life of Iranian women diagnosed with this syndrome. Materials and Methods A total of 796 women diagnosed with polycystic ovary syndrome, aged 15–49 years, completed the questionnaires, interviews, and medical assessments required for this study. A reliable and validated Persian version of the health-related quality of life questionnaire for polycystic ovary syndrome patients was used. Linear regression models were used to assess the association between the symptoms of polycystic ovary syndrome and health-related quality of life. Results The mean age of participants was 28.02 years. 35.4% of the subjects were classified as overweight or obese. Hirsutism, was reported to have the strongest impact on the patients’ health-related quality of life, followed in descending order by body mass index, irregular menses and infertility. The relative level of hirsutism was directly proportional to decrease in health-related quality of life score (p<0.001). Conclusions The results of the study found that hirsutism had the strongest impact on the health-related quality of life measures in Iranian women diagnosed with polycystic ovary syndrome. Health care officials need to evaluate in depth the effect of each clinical feature of polycystic ovary syndrome separately and design management strategies, keeping in mind the psychological and physical manifestations.